The Art of Melodeclamation. Studies on the Origin of Rap Music - Kwiatkowski, Maciej (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
The article focus on problematic associated with beggining of rap music. Studying oldest songs from genre showing, that in most instances, people rapping for fun or to encourage other in participation in it. Author probe not only first rap songs and rap artists, but also music extraction, which arise from inspiration some type of music, like blues, funk, or jazz. Analise few singles from 70. and 80. trying answer on question, why some tracks were so popular. By specyfic of subject, text vicariously keeping on city culture of New York, previous century in United States.